2018
DOI: 10.26740/jptt.v9n1.p62-76
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran E-Learning Perkembangan Anak di Jurusan Psikologi

Abstract: Conventional learning method is viewed to be less effective because it poses the problems of space and time. Information Technology offers a method for more effective online learning called e-learning. This research aims to develop e-learning for the module of Child Development at Department of Psychology Universitas Negeri Surabaya. This study was a developmental research project that used the method of ADDIE (Analysis, Design, Development, Implementation, Evaluation). This model was chosen because the stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…The appropriate understanding level might be because of the new learning system that attracts the students. The result of this analysis is in line with the results of the research conducted by Karwati (2014), Nasution (2017) and Khoirunnisa et al, (2018) which concluded that discussion forums and provided learning materials in e-learning system helped the students to get more knowledge and to increase their understanding level. The submitted materials, furthermore, are accessible at any time and any place that can ease the students to review and deepen their understanding upon them (Karwati, 2014;Nasution, 2017).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The appropriate understanding level might be because of the new learning system that attracts the students. The result of this analysis is in line with the results of the research conducted by Karwati (2014), Nasution (2017) and Khoirunnisa et al, (2018) which concluded that discussion forums and provided learning materials in e-learning system helped the students to get more knowledge and to increase their understanding level. The submitted materials, furthermore, are accessible at any time and any place that can ease the students to review and deepen their understanding upon them (Karwati, 2014;Nasution, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…The submitted materials, furthermore, are accessible at any time and any place that can ease the students to review and deepen their understanding upon them (Karwati, 2014;Nasution, 2017). The discussion forum as a feature in the e-learning system has become one of the platforms for students to discuss things regarding the upcoming learning materials (Kurniawan, Suprianto, and Sumardiyono, 2016;Sinaga, 2015;Khoirunnisa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online learning is a form of learning method that is perceived to be student-centered. According to Khoirunnisa (2018), the role of educators can be described as active facilitators, namely providing material to be explored for students and guiding students…”
Section: Introductionmentioning
confidence: 99%
“…2019; Imansari & Sunaryantiningsih, 2017;Khoirunnisa et al, 2018;Udayana et al, 2017). Di era revolusi industri 4.0 dan sesuai dengan pembelajaran abad 21 banyak dikembangkan modul berupa modul elektronik atau e-modul (Elvarita et al, 2020;Wijayanti et al, 2016), sehingga pemilihan multimedia sebagai media pembelajaran sangat tepat dilakukan.…”
unclassified